Retinoic acid receptor γ is a therapeutically targetable driver of growth and survival in prostate cancer. Issue 6 (3rd September 2020) - Petrie, Kevin; Urban‐Wójciuk, Zuzanna; Sbirkov, Yordan; Graham, Amy; Hamann, Annika; Brown, Geoffrey
Abstract: Background: Prostate cancer (PC) tissue contains all‐ trans retinoic acid (ATRA) at a very low level (10 −9 M), at least an order of magnitude lower than in adjacent normal healthy prostate cells or benign prostate hyperplasia. When this is coupled with deregulated expression of the intracellular lipid‐binding proteins FABP5 and CRABP2 that is frequently found in PC, this is likely to result in the preferential delivery of ATRA to oncogenic PPARβ/δ rather than retinoic acid receptors (RARs). There are three isotypes of RARs (RARα, RARβ, and RARγ) and recent studies have revealed discrete physiological roles. For example, RARα and RARγ promote differentiation and self‐renewal, respectively, which are critical for proper hematopoiesis. Aims: We have previously shown that ATRA stimulates transactivation of RARγ at sub‐nanomolar concentrations (EC50 0.24 nM), whereas an 80‐fold higher concentration was required for RARα‐mediated transactivation (EC50 19.3 nM). Additionally, we have shown that RAR pan‐antagonists inhibit the growth of PC cells (at 16‐34 nM). These findings, together with the low level of ATRA in PC, led us to hypothesize that RARγ plays a role in PC pathogenesis and that RARγ‐selective antagonism may be an effective treatment. Methods and results: We found that concentrations of 10 −9 M and below of ATRA promoted survival/proliferation and opposed adipogenic differentiation of human PC cell lines by a mechanism that involves RARγ. We also found that a RARγ‐selective antagonist (AGN205728) potently induced mitochondria‐dependent, but caspase‐independent, cell death in PC cell lines. Furthermore, AGN205728 demonstrated synergism in killing PC cells in combination with cytotoxic chemotherapeutic agents. Conclusion: We suggest that the use of RARγ‐selective antagonists may be effective in PC (and potentially other cancers), either as a single agent or in combination with cytotoxic chemotherapy.